Negative reactivity and parental warmth in early adolescence and depressive symptoms in emerging adulthood. (1st July 2016) - Lloyd, Brendan; Macdonald, Jacqui A.; Youssef, George J.; Knight, Tess; Letcher, Primrose; Sanson, Ann; Olsson, Craig A.
Abstract : Objective: Cross‐sectional research suggests that relationships between temperamental negative reactivity and adolescent depressive symptoms may be moderated by parental warmth. The primary purpose of this study was to conduct the first prospective analysis of this relationship. Method: Data from 1, 147 families in an Australian population‐based longitudinal study were used to examine: (1) temporal relationships between negative reactivity in early adolescence (13–14 years) and depressive symptoms in emerging adulthood (19–20 years); (2) the moderating role of parent‐reported warmth in early adolescence (13–14 years); and (3) the moderating role of child gender. Hierarchical multiple regression was conducted to test the hypothesis that parental warmth would moderate the relationship between early adolescent negative reactivity and depressive symptoms in emerging adulthood. Results: After accounting for previous depressive symptoms at age 13–14 years, negative reactivity was positively associated with later depressive symptoms. By contrast, parental warmth at 13–14 years was negatively associated with later depressive symptoms for females but not males. Parental warmth did not moderate the association between early adolescent negative reactivity and subsequent depressive symptoms. Conclusions: This study was the first to use prospective data to assess the protective effects of early adolescent parental warmth on the association between negative reactive temperaments and early adult depressive symptoms. Findings suggest that parental warmth for negatively reactive children provides only concurrent protection against subsequent depressive risk. This study did not examine parent–child transactional models, which may, in future longitudinal research, improve understanding of how trajectories of parent–child goodness‐of‐fit contribute to depressive symptoms.